Formation and Identification of a 5-(Hydroxymethyl)-2-Furfural-Zingerone Condensate and Its Cytotoxicity in Caco-2 Cells - Ke, Yujing; Yin, Zhao; Chen, Nenghua; Chen, Peifang; Liu, Jie; Ou, Shiyi; Li, Guoqiang (Frontiers in Nutrition, 2022)
5-(Hydroxymethyl)-2-furfural (HMF), an active furfural, widely exists in various food products and has potential safety risks. It can be eliminated by occurring aldol condensation with α-unsubstituted ketones in the presence of catalysts. However, the elimination process between HMF and ketones from food is rarely studied. In this study, the adduct formation between HMF and zingerone (ZGR) catalyzed by proline was investigated. It revealed that the adduct formation led to 99.75% of HMF being trapped under the optimized reaction condition. Moreover, the in vitro digestion stability of HMF-ZGR adduct (HMZ) and its cytotoxicity against Caco-2 cells were evaluated. The results indicated that more than 75% of HMZ was remained after a three-stage simulated digestion. Following 24 and 48 h of incubation, HMZ exhibited cytotoxicity against Caco-2 cells with IC50 values of 41.47 ± 5.33 and 25.39 ± 3.12 mM, respectively, versus 35.39 ± 4.03 and 19.17 ± 2.10 mM by HMF.